2020
DOI: 10.1039/d0sc04350h
|View full text |Cite
|
Sign up to set email alerts
|

Transferrable property relationships between magnetic exchange coupling and molecular conductance

Abstract: Calculated conductance through Aun–S–Bridge–S–Aun constructs are compared to experimental magnetic exchange coupling parameters in TpCum,MeZn(SQ–Bridge–NN) complexes, where SQ = semiquinone radical and NN = nitronylnitroxide radical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Molecular junctions are not the only method by which charge transport along a molecular backbone can be investigated. 78 OAE derivatives also find use as bridging units between functional groups in donor-bridge-acceptor (D-B-A) systems, [79][80][81] mixed valence complexes 82,83 and biradical systems. 84 Such studies are outside the scope of this review.…”
Section: A History Of Oaes In Molecular Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular junctions are not the only method by which charge transport along a molecular backbone can be investigated. 78 OAE derivatives also find use as bridging units between functional groups in donor-bridge-acceptor (D-B-A) systems, [79][80][81] mixed valence complexes 82,83 and biradical systems. 84 Such studies are outside the scope of this review.…”
Section: A History Of Oaes In Molecular Electronicsmentioning
confidence: 99%
“…104 Related attenuation factors are observed for electron transfer in D-B-A systems and magnetic exchange coupling in biradical systems. 78 However, these values are not directly comparable because different exchange interactions and tunnelling energy barriers will exist in the backbones under the very different experimental conditions. 239 Many studies have experimentally determined values of β for OAEs.…”
Section: Impact Of Molecular Length On Conductancementioning
confidence: 99%
“…Molecular electronic coupling figures prominently in electron transfer rates and electron transport efficiency involving molecular bridges (B) that span donor and acceptor units in molecules (D-B-A) and in biased electrodes/molecular break junctions (M-B-M), respectively. Electronic coupling has been suggested to be a transferable property of the molecular bridge, , enabling further relationships between electron transfer/transport and the bridge-dependent magnetic superexchange interaction to be developed. Understanding the nature of electronic and magnetic communication will enhance our ability to design bespoke electronic, spintronic, and related molecular or molecule-based devices. Electronic coupling through alternant organic π-systems ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the nature of electronic and magnetic communication will enhance our ability to design bespoke electronic, spintronic, and related molecular or molecule-based devices. Electronic coupling through alternant organic π-systems ( e.g. , benzene) has been studied extensively and can be illustrated by topographical models and concepts such as resonance, aromaticity, and cross-conjugation. , Recently, this has been exploited to relate the magnetic exchange interaction with molecular conductance and rectification mediated by alternant and alternant-like organic π-systems. , In spite of our knowledge of electronic and magnetic coupling in alternant systems, the corresponding coupling through nonalternant π bridges is markedly less understood. , This is exemplified by the fact that computationally aided analysis of, and transport through, the nonalternant π-system of azulene has produced both debate and seemingly conflicting experimental results. As a quintessential nonalternant π-system, azulene has been of interest for nearly five decades for its unique photophysical, optical, and electronic properties and has gained renewed interest as a key molecule in organic electronics. , Despite their technological importance, there is a paucity of studies directed toward understanding the nature of the electronic and magnetic coupling mediated by azulenes and related nonalternant systems. ,, A rare example of magnetic communication through a nonalternant π-system was recently described by Haraguchi et al , who reported differential magnetic exchange coupling of iminonitroxides (IN) and nitronylnitroxides (NN) covalently attached to the 1,3-positions of azulene ( 1,3-IN 2 Az and 1,3-NN 2 -Az , Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the charge-separated Kekulé resonance structure in Figure A incorrectly predicts antiferromagnetic coupling in 1,3-SQ 2 Az , the corresponding structure (Figure B) correctly predicts antiferromagnetic coupling in 1,3-SQ 2 Fc . The correlation of bridge-mediated magnetic exchange parameters, J , and molecular conductance, G , ,, suggests that the graphical method of Markussen might be used to predict exchange coupling through an Fc Cp ring. Figure C illustrates this method for Cp and Az bridges.…”
mentioning
confidence: 99%